Arthroscopic Lysis of Adhesions for Stiffness After Surgical Management of Proximal Humerus Fractures Leads to Satisfactory Outcomes in Most Patients - Javier Ardebol, M.D; Nicholas A. Zuk, M.D; Ali Īhsan Kiliç, M.D; Theresa Pak, D.O; Mariano E. Menendez, M.D; Patrick J. Denard, M.D (Elsevier, 2023)
Purpose: To report patient-reported outcomes (PROs), range of motion (ROM), and satisfaction, in patients who underwent arthroscopic lysis of adhesions for stiffness after open reduction with internal fixation (ORIF) or reverse shoulder arthroplasty (RSA) for fracture. Methods: A retrospective review was performed to identify patients with stiffness who underwent arthroscopic lysis of adhesions following ORIF or RSA for proximal humerus fracture at a single institution between 2012 and 2021 with minimum 1-year follow-up. PROs including visual analog scale for pain (VAS), American Shoulder and Elbow Surgeons (ASES), and Subjective Shoulder Value (SSV), as well as active ROM including forward flexion (FF), external rotation (ER), internal rotation (IR), were collected pre- and postoperatively. Attempted nonoperative treatment before arthroscopic lysis of adhesions was documented. Complications and satisfaction were also recorded. Results: A total of 21 patients met the study criteria (4 RSA, 17 ORIF), with an average age of 66.7 ± 8 years. The study sample comprised mostly of female patients (90%). The mean time from the index surgery to arthroscopy was 9 months, and mean follow-up post-lysis was 17 months. Patients with ORIF reported significant pain relief (VAS, Δ -3.2) and improvement in range of motion (FF, Δ 36°; ER, Δ 20°; IR Δ 3 spinal levels) and PROs (ASES, Δ 34.7; SSV Δ 44.8) (P < .01) after lysis. Patients with RSA had significant improvement in ASES (Δ 21.8; P = .04), SSV (Δ 8.8; P = .04), and FF (Δ 38; P = .02) but did not have significant improvement in VAS (Δ -2; P = .2), ER (Δ 0°; P = 1.0), and IR (Δ 1 spinal level; P = .2). Satisfaction was 100% in the RSA cohort and 82% in the ORIF cohort. No complications were observed. Conclusions: Arthroscopic lysis of adhesions for stiffness after surgical management of proximal humerus fracture leads to satisfactory outcomes in most patients. Post-ORIF, patients may achieve improvement in PROs and global ROM, whereas post-RSA, patients may achieve improvement in PROs and FF but do not necessarily improve in rotational ROM. Level of Evidence: Level IV, therapeutic case series.